Yöbaarin tyttö ; Siniset linnut - Randelin, Kake, 1955-; Finnlevy ([Helsinki] : Fazer Finnlevy, 1989)
2 kappaletta.
Kake Randelin (lauluääni), yhtye.
[Äänite]
Keywords: Randelin, Kake, -- 1955- -- singlet; iskelmät